2021
DOI: 10.3390/microorganisms9010098
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Antimicrobial Resistance in the Streptococcus bovis/Streptococcus equinus Complex (SBSEC) Isolated from Korean Domestic Ruminants

Abstract: S. bovis/S. equinus complex (SBSEC) includes lactic acid-producing bacteria considered as the causative agent associated with acute rumen lactic acidosis in intensive ruminants. Considering the limited information on the detailed characteristics and diversity of SBSEC in Korea and the emergence of antimicrobial resistance (AMR), we investigated the diversity of SBSEC from domestic ruminants and verified the presence of antimicrobial resistance genes (ARGs) against several antimicrobials with their phenotypic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Studies on animal feces have reported changes in antimicrobial resistance. A Korean study on ruminant animals specifically studied SBSEC bacteria and their antibiotic sensitivities, showing intermediary susceptibility to tetracycline, erythromycin, and clindamycin [ 14 ]. Variable resistance rates have been reported for clindamycin, erythromycin, tetracycline, and levofloxacin [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on animal feces have reported changes in antimicrobial resistance. A Korean study on ruminant animals specifically studied SBSEC bacteria and their antibiotic sensitivities, showing intermediary susceptibility to tetracycline, erythromycin, and clindamycin [ 14 ]. Variable resistance rates have been reported for clindamycin, erythromycin, tetracycline, and levofloxacin [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to report the biological and genetic properties of both lytic phages infecting representative SBSEC, thereby leading to the potential control of ruminal microbiota (Table 2 ). The isolated phages have largely infected the SBSEC of both type strains and wild isolates from the rumen 21 . Interestingly, the isolated phages showed broad lytic activity against other lactic acid-producing bacteria, such as Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…lactis KCCM 41572 T were used in this study, as listed in Table 1 . Among the 59 SBSEC strains used in this study, 51 were previously identified as SBSEC members based on sodA gene sequence analysis and their potential genetic diversity has been determined 21 . All the strains were cultured in tryptic soy agar (TSA; Difco, USA) at 37 °C for 24 h and stored in tryptic soy broth (TSB; Difco, USA) with 10% glycerol at -80 °C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, several studies observed that supplementation with ionophore antibiotics could decrease the ruminal bacteria (especially gram-positive bacteria) in a high concentrate diet, thereby preventing a severe decrease of ruminal pH [ 38 40 ]. However, the potential for antibiotic resistance in ruminal bacteria has made it impossible to use ionophore antibiotics as a feed additive to modulate rumen fermentation [ 41 , 42 ]. The present study is the first trial presenting a new strategy to control S. bovis specifically using endolysin.…”
Section: Discussionmentioning
confidence: 99%